Corporate risk reporting: analysis of risk disclosures in the interim reports of public Portuguese non-financial companies - Serrasqueiro, R. M. (2018)
Fast changing environments, globalization, coupled with financial scandals, and the advance of information technologies made corporate risk a very central issue in management and accounting. Current governance codes require that management disclose in annual reports its responsibility for the adequacy of risk management and internal control systems and the disclosure of risk and uncertainties faced by companies are required by both governance codes and corporate reporting. This study seeks to capture risk disclosure patterns adopted by public Portuguese companies in interim reports and to investigate whether the audit quality may explain the observed risk disclosures practices. Manual content analysis has been carried out in the interim reports of 35 non-financial Portuguese firms ranked by decreasing market capitalization to create indexes of corporate risk disclosure, which have been used for observing the tone of disclosure and for testing an explanatory model with proxies of audit quality together with other explanatory variables widely used in disclosure research. Results point out that quantified risk disclosure prevails in interim reports and that firm’s risk disclosure policies are not influenced by auditor’s quality. This work contributes to academic and regulatory environments, filling the gap about risk disclosure in the interim report, identifying the nature of corporate risk disclosures, assessing the quality of risk information and updating research about determinants of risk disclosure in interim reports.